Forest, water and people: The roles and limits of mediation in transforming watershed conflict in Northern Thailand - Ahmad Dhiaulhaq; Kanchana Wiset; Rawee Thaworn; Seth Kane; David Gritten (Forest and Society, 2017)
This study focuses on watershed management in Northern Thailand, where conflict over forest, land and water-use is a prevailing problem. A characteristic of watershed conflicts is that they are often multifaceted and involve multiple stakeholders with different interests and values, consequently requiring conflict management approaches that are sustainable in their outcomes, including addressing the underlying causes of the conflicts. Drawing from a case study in Mae Tia Mae Tae watershed in Northern Thailand, this study explores how mediation by external third party can contribute to the transformation of conflicts in the watershed and how the broader institutional contexts in which the conflict is embedded shapes the mediation outcomes. The study suggests that co-creation of mutual understanding and recognition of each party’s socio-cultural differences, including land-use practices, are critical in building trust and in how conflict transformation processes moved forward. Moreover, the ability of the mediator in facilitating the establishment of a deliberative institution (i.e. a watershed network committee) and agreed rules on forest utilization were also critical in maintaining long-term collaboration in the watershed and potentially preventing other conflicts arising in the future. Some issues, however, may threaten the continuity of the cooperation and sustainability of peace in the watershed, including the lack of structural reform that formally recognizes local people’s rights, insecure land tenure, and the absence of legal recognition for the watershed network committee as a legitimate mechanism for watershed decision making. The paper discusses these findings by comparing it with those from our previous studies in other locations (Cambodia, Indonesia and Western Thailand) to strengthen the insights from Northern Thailand. Finally, the research puts forward some recommendations for reforms and to strengthen the use of effective mediation, to achieve transformative outcomes, in conflicts of this nature. iation, to achieve transformative outcomes, in conflicts of this nature.